The tapestry of knowledge : Manufacturing engineering research. (volume 3) - Lau, Kok Tee (Penerbit UTeM Press, 2024)
The third volume of The Tapestry of Knowledge: Manufacturing Engineering Research presents recent research findings focusing on the field of manufacturing engineering, with broad coverage of topics related to manufacturing systems, engineering materials, manufacturing processes, and manufacturing automation. This book emphasizes advancements that bridge the theoretical framework with practical applications. It highlights various examples and real applications of advanced tools and techniques in implementing engineering solutions. This book serves as a platform for academic exchange among experts, scholars, researchers, and students to advance the state of the art and benefit society.